Implementation Of The Educational Module As An Effort To Form Teeth Brushing Behavior In Clients At The Bnn Rehabilitation Center - Hasriyani Hasriyani; Nurwiyana Abdullah; Neni Kurniati Majid; Endah Aryati Eko Ningtyas (Poltekkes Kemenkes Semarang, 2023)
Dental health, which is part of general health, is still a problem that needs to be addressed. Data from the World Health Organization (WHO) 2022 reports that the world's dental and oral health status in the form of dental and oral disease occurs in almost 3.5 billion people throughout the world, and an estimated 2 billion people suffer from dental caries. According to 2018 Basic Health Research (RISKESDAS) data, 57.6% experienced dental and oral problems. Factors that influence a person's dental and oral health status come from behavior, environment and health services. The aim of brushing teeth is to prevent dental caries and maintain oral and dental hygiene. People who use drugs experience dental and oral health problems. Poor oral and dental hygiene causes diseases such as dental caries, xerostomia or dry mouth, rampant caries, bleeding gums, a burning sensation, stomatitis, changes in the chemical composition of saliva, abscesses and decreased immunity. Community service activities carried out at the BNN Baddoka Makassar rehabilitation center, South Sulawesi. The sample used was 11 people. The method used in this activity is the Health system approach, namely: Input – Process – Output. The results showed an increase in client knowledge at the Baddoka BNN Rehabilitation Center after education was carried out using the module. Keyword : Dental hygiene; caries; drugs; brushing teeth